The role and challenges of ethics in daily life - Falla De Güich, Myriam (2018)
This article tries to reflect on morality in everyday life and the urgent decision making to which the human individual is constantly subject. The moral subject is constantly faced with a variety of dilemmas, which is why it is necessary to think in an ethical way about the exits in cases of greater attention.